Temporal Analysis of Lipopolysaccharide-Induced Sickness Behavior in Virgin and Lactating Female Rats - Nascimento, Amanda; Bernardi, Maria [UNESP]; Pecorari, Vanessa [UNESP]; Massoco, Christina; Felicio, Luciano (Karger, 2013)
Objectives: Lipopolysaccharide (LPS), an endotoxin that originates from the cell wall of Gram-negative bacteria, activates the immune system to release proinflammatory cytokines and to induce sickness behavior. The present study sought to characterize the time-dependent effects of LPS on fever, body weight, and food and water consumption in female virgin and lactating rats exposed to an LPS dose previously reported to induce sickness behavior in pregnant female rats. Methods: Virgin female Wistar rats in the estrous phase and lactating female Wistar rats on the third day of lactation received 100 mu g/kg LPS or saline solution. Tympanic temperature, body weight, and food and water consumption were assessed 0, 2, 24, 48, 72, 96, and 120 h after treatment. Results: In lactating female rats, tympanic temperature was attenuated compared with virgin females. Food consumption and body weight gain in both groups decreased, but lactating rats consumed more food than virgin rats. Water consumption increased at different time points. Conclusion: LPS exposure induced several signs of sickness behavior, including decreases in food consumption and body weight gain, and induced adipsia in both virgin and lactating female rats. Because the time course and profile of fever varied between lactating and nonlactating animals, these responses appeared to depend on the physiological state of female animals. Copyright (C) 2013 S. Karger AG, Basel
Keywords: Fever; Lactating female; Virgin female; Lipopolysaccharide